Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd007017
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical policies: effects of cap and co-payment on rational drug use

Abstract: We found a diversity of cap and co-payment policies. Poor reporting of the intensity of interventions and differences in setting, populations and interventions made it difficult to make comparisons across studies. Cap and co-payment polices can reduce drug use and save plan drug expenditures. However, although insufficient data on health outcomes were available, substantial reductions in the use of life-sustaining drugs or drugs that are important in treating chronic conditions may have adverse effects on heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 65 publications
4
98
0
9
Order By: Relevance
“…Our finding that a substantially higher proportion of patients with these plans The Emergency Severity Index is a validated measure of severity of illness at the time of presentation to an emergency department, and is used to stratify patients into five groups (Level 1 = most severe; Level 5 = least severe) for triage priority experienced cost-related barriers to filling prescriptions than did privately insured patients is likely due to the finding of numerous prior studies that cost sharing at even very low levels impedes access to care for low-income patients. [18][19][20][21][22] A different explanation may hold for our finding that more patients with Medicaid and Commonwealth Care Type 1 than with private insurance reported delaying or not getting dental care due to cost, as these publicly subsidized plans cover basic preventive dental services, but not more extensive dental work. Our finding that Medicaid patients also reported cost-related For patients with Commonwealth Care Type 2 and 3 plans, cost sharing can be more substantial and indeed, we found cost-related barriers to care for services where cost sharing was particularly high.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that a substantially higher proportion of patients with these plans The Emergency Severity Index is a validated measure of severity of illness at the time of presentation to an emergency department, and is used to stratify patients into five groups (Level 1 = most severe; Level 5 = least severe) for triage priority experienced cost-related barriers to filling prescriptions than did privately insured patients is likely due to the finding of numerous prior studies that cost sharing at even very low levels impedes access to care for low-income patients. [18][19][20][21][22] A different explanation may hold for our finding that more patients with Medicaid and Commonwealth Care Type 1 than with private insurance reported delaying or not getting dental care due to cost, as these publicly subsidized plans cover basic preventive dental services, but not more extensive dental work. Our finding that Medicaid patients also reported cost-related For patients with Commonwealth Care Type 2 and 3 plans, cost sharing can be more substantial and indeed, we found cost-related barriers to care for services where cost sharing was particularly high.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their rational underpinning, a large body of research has accumulated over the past four decades detailing the negative impact of prescription copayments on prescription drug use and subsequent health outcomes. [1][2][3] Most studies have found that as the price of the copayment increases, patients reduce their adherence to essential life-prolonging drugs that are used in the treatment of chronic disease. [1,4,5] Copayments for prescription drugs are therefore directly and indirectly associated with increased morbidity, mortality and increased health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Most studies have found that as the price of the copayment increases, patients reduce their adherence to essential life-prolonging drugs that are used in the treatment of chronic disease. [1,4,5] Copayments for prescription drugs are therefore directly and indirectly associated with increased morbidity, mortality and increased health care costs. [3,[6][7][8] While the results of previous research on copayments are mostly consistent, the majority of studies included in existing systematic reviews have been conducted in the U.S. and Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutical expenditure is also a key indicator in international comparisons. The development of pharmaceutical expenditure at national level or in international comparisons is subject to several analyses, such as assessing the effect of pharmaceutical policies or forecasting future trends [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%